Experimental study of gas pressure drop in rotating packed bed with rotational‐stationary packing. (25th August 2017) - Liu, Xuewu; Jing, Manjun; Chen, Shuhua; Du, Leilei
Abstract: Rotating packed bed (RPB) with rotational‐stationary packing is a novel instrument that could greatly enhance mass transfer compared with the conventional packed columns. The structure of rotational‐stationary packing makes the gas repeatedly enter the packing to increase the end effect. Meanwhile, owing to the resistance of the packing to the gas, the gas pressure drop of rotating packed bed with rotational‐stationary packing becomes the necessary factor that can evaluate the equipment. The gas pressure drop of the dry bed and wet bed were determined at various operating variables, including the rotational speed, the gas flow rate, and the liquid flow rate. In this work, the gas pressure drop was classified on the basis of the gas flow path and the corresponding theoretical formulas were provided. The pressure drop of the dry bed increased with increasing rotational speed and gas flow rate was observed, and the liquid flow rate had little influence on the pressure drop of the wet bed. Finally, the experimental values were fitted to the theoretical formula and the relationship between total pressure drop and rotational speed, gas flow rate in a RPB with rotational‐stationary packing was presented. The theoretical calculated values agreed well with the experimental data with a deviation within 6 %. These will provide the gas pressure drop theoretical calculation formula for a kind of RPB with rotational‐stationary packing.